Guaranteeing indigenous people's rights in Latin America : progress in the past decade and remaining challenges - summary (United Nations SantiagoCL, 2014)
Aims to provide an update on progress and challenges concerning the rights of indigenous peoples in Latin America in conjunction with the indigenous peoples of the region and to contribute substantively to an evaluation of the past decade and to identify post-2014 actions for discussion at the 2014 World Conference on Indigenous Peoples.
Keywords: INDIGENOUS POPULATION